2017
DOI: 10.1007/s41207-017-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature carbonization of chicken manure to char and its effect on growth of Oryza sativa L. Koshihikari and Brassica rapa komatsuna

Abstract: Considering the demand for transforming poultry waste into eco-friendly manure, we carbonized chicken manure at 402, 449 and 528°C and determined the physicochemical properties. We evaluated the effectiveness of the ensuing carbonized chicken manure (CCM) as a fertilizer using Brassica rapa, var. komatsuna and Oryza sativa L., var. japonica, cv. Koshihikari, in the upland and the paddy field soil, respectively. Herein, we carried out duplicate treatment of CCM (carbonized at 528°C) either alone or in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This has serious negative implications for the use of carbonized CM for sustainable production of crops. Indeed, Steiner et al [12] already observed negative effects on the quality of ryegrass due to the decreased N supply ability of CM carbonized at 500 • C. The results of Ishimori et al [11] on plant growth and yield indicated that carbonized CM at 528 • C cannot supply sufficient N to independently support plant productivity.…”
Section: Connection Between the Chemical Alteration And N Supply Ability Of CM During Carbonization At Different Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…This has serious negative implications for the use of carbonized CM for sustainable production of crops. Indeed, Steiner et al [12] already observed negative effects on the quality of ryegrass due to the decreased N supply ability of CM carbonized at 500 • C. The results of Ishimori et al [11] on plant growth and yield indicated that carbonized CM at 528 • C cannot supply sufficient N to independently support plant productivity.…”
Section: Connection Between the Chemical Alteration And N Supply Ability Of CM During Carbonization At Different Temperaturesmentioning
confidence: 99%
“…For instance, Tagoe et al [10] observed an increase in total N content of soybeans and a 43% increase in seed yield of the plant after application of CM that was carbonized at 500 • C. In addition, Chan et al [3] observed a 96% increase in radish yield and a significant increase in tissue N content over that of the control for CM, which was carbonized at 450 and 550 • C. With these results, they established that carbonized CM produced around these temperatures can supply sufficient plant nutrients, including N, for sustainable plant productivity. On the contrary, Ishimori et al [11] reported that CM carbonized at 528 • C alone cannot support the normal growth of plants after they observed that Oryza sativa and Brassica rapa komatsuna were not significantly different in their growth in plots of carbonized CM and the control. Steiner et al [12] found lower concentrations of N in tissues of plants fertilized with CM that was carbonized at 500 • C when compared to the unfertilized control, and concluded that "N in carbonized CM is not plant available".…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The up arrows and down arrows represent, respectively, the increasing and decreasing responses of the parameters by biochar application . References : (1) Zhang et al, 2016 ; (2) Liu et al, 2014 ; (3) Bian et al, 2014 ; (4) Qian et al, 2014 ; (5) Zhao et al, 2014 ; (6) Zheng et al, 2013 ; (7) Ishimori et al, 2017 ; (8) Kameyama et al, 2017 ; (9) Koyama and Hayashi, 2017 ; (10) Guerena et al, 2013 ; (11) Yao et al, 2012 ; (12) Ippolito et al, 2016 ; (13) Cayuela et al, 2013 ; (14) Olmo et al, 2014 ; (15) Kammann et al, 2011 ; (16) Reibe et al, 2015 ; (17) Bruun et al, 2012 ; (18) Agegnehu et al, 2016 ; (19) Mete et al, 2015 ; (20) Tammeorg et al, 2014 ; (21) Yamato et al, 2006 ; (22) Haefele et al, 2011 . …”
Section: Properties Of Biochar: the Current State Of Knowledgementioning
confidence: 99%